Who is empowered? Predictors of empowerment in Bangladesh and Ghana - Martinez, Elena (International Food Policy Research Institute, 2019)
Presented by Elena Martinez (International Food Policy Research Institute), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.